Identification of social commerce service quality (SCSQ) dimensions for Malaysian modest fashion industry - Hanafi, Nurul Izzati; Islam, Rafikul; Maulan, Suharni (UUM Othman Yeop Abdullah Graduate School of Business, 2023)
The purpose of this study is to identify emerging themes in the Social Commerce Service Quality (SCSQ) that are appropriate for the Malaysian modest fashion industry to improve the online shopping experience for Malaysian consumers. This qualitative research applied semi-structured online interviews that include nine respondents from Malaysian modest fashion sellers, direct and indirect distributors, and buyers. Thematic analysis was used to analyze the participants' responses in determining and identifying the SCSQ dimensions. Eight themes are identified which are Social Interaction Quality, Functional Quality, Design Quality, Information Quality, Privacy and Security, Responsiveness, Personalization, and Communication Quality. Notably, Personalization and Communication Quality are two newly discovered in the Malaysian modest fashion industry context. The results offer helpful guidance for Malaysian modest fashion businesses to allocate their resources prudently.